ЗМЕНШЕННЯ ВТРАТ АКТИВНОЇ ПОТУЖНОСТІ В ГРОЗОЗАХИСНОМУ ТРОСІ ДВОКОЛОВОЇ ПОВІТРЯНОЇ ЛІНІЇ ЕЛЕКТРОПЕРЕДАЧІ ШЛЯХОМ ЗМІНИ РОЗТАШУВАННЯ ЇЇ ФАЗ - Красножон, А.В.; Пентегов, І.В.; Красножон, О.В.; Тимошенко, З.О. (Інститут електродинаміки Національної академії наук України, 2018)
A low-cost method is proposed for reducing active power losses in grounding wires of double-circuit overhead power lines of traditional design, the essence of which is to change the spatial arrangement of the phases of different circuits of a double-circuit power line. Using the example of a double-circuit power line with a voltage of 330 kV, it is shown that the proposed method allows to achieve a significant reduction in losses in the wire and increase the efficiency of electric power transmission. The problem considered is topical, both in case of construction of new overhead power lines and in case of modernization of existing ones. References 6, figures 3.